Aux communeux - La Commune révolutionnaire
"Le groupe : La commune révolutionnaire Aberlen, Berton, Breuillé, Carné, Jean Clément, F. Cournet, Ch. Dacosta, Dellés, A. Derouilla, E. Eudes, H. Gausseron, E. Gois, A. Gouillé, E. Granger, A. Huguenot, E. Jouanin, Ledrux, Léonce, Lhuillier, P. Mallet, Marguerittes, Constant-Martin, A. Moreau, H. Mortier, A. Oldrini, Pichon, A. Poirirer, Rysto, B. Sachs, Solignac, Ed. Vaillant, Varlet, Viard. Londres, juin 1874"